(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Objective: The aim of the study is to screen the phytochemicals present in the Red Grape Seed (Vitis vinifera .L), Tinospora cordifolia and Phyllanthus emblica fruit extracts . Methodology: Red grapes (Vitis vinifera.L), Tinospora cordifolia and Phyllanthus emblica Extracts were found to provide a wide range of health promoting and health protecting properties, exhibiting plenty of potential compounds to screen and exhibit different varieties of polyphenolic compounds. Phytochemicals are organic chemical elements that exist naturally in plants and have positive effects on human health. Results: The extracts of Red Grape Seed, Tinospora cordifolia and Phyllanthus emblica shows the presence of polyphenolic compounds such as flavonoids, isoflavonoids, anthocyanidins, phytoestrogens, terpenoids, carotenoids, limonoids, phytosterols, glucosinolates and fibres as well as alkaloids, glycosides and polyphenols. The phytochemicals are typically created by a variety of metabolic processes in plants. They are crucial in defending plants against environmental dangers including stress, drought, pathogenic attack etc. Conclusion: The findings of this study clearly demonstrate the significant influence of Red Grape (Vitis vinifera.L) Seed , Tinospora cordifolia and Phyllanthus emblica fruit extracts on the healthcare system and its potential to offer medical benefits, such as the prevention and treatment of Neurological and Physiological diseases.